Instructional materials in communication arts for grade IV based on the individualized instruction approach with accompanying notes for the teacher - Afos, Clemencia P. 1931-
This paper consists of instructional materials in Communication Arts for Grade IV based on the individualized instruction approach. The author studied the BPS guide in English and the course outlines in social studies and in health and science for Grade IV. She then drew a framework based on linguistic and psycholinguistic principles of second language teaching. Objectives for the course were then set and the scope and sequence charts were prepared.